Business Hack By Digital - Amir, Irham (Tamkin Jurnal Pemberdayaan Tazkia, 2023)
The fact is that many Indonesian students who study at Al-Azhar do not know the latest basic concepts of entrepreneurship, so they cannot maximize their business potential. from this motivation, Improving entrepreneurship skills for the younger generation Creating quality, creative human resources as a provision for entrepreneurship; (iii) building business networks and creating youth entrepreneurs. For participants, this activity is expected to add insight in maximizing digital marketing to develop start-up businesses. For IAI Tazkia, For business actors, this activity is expected to increase understanding of business actors regarding the steps to starting and growing the business using prototype business models and appropriate marketing tools. so that it can create entrepreneurs from the younger generation who can make good use of digital technology.